Contribution of the payments for environmental services (SPA) in the restoration of secondary forests in Hojancha,Costa Rica - Murakami Bello, S. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- IICA, Turrialba (Costa Rica), 2008